2002
DOI: 10.1007/s005340200026
|View full text |Cite
|
Sign up to set email alerts
|

Prospective assessment of the safety and benefit of laparoscopic liver resections

Abstract: Liver resections of up to two segments can be performed by laparoscopy using the same technique as that used during open surgery. However, the benefits observed compared with open surgery appear to be limited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
121
1
9

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(137 citation statements)
references
References 40 publications
6
121
1
9
Order By: Relevance
“…They include benign (adenoma and symptomatic focal nodular hyperplasia, haemangioma or giant liver cysts) and malignant (both primary and metastatic) lesions in the liver, and living donor liver harvesting. A high percentage of benign tumours was presented in early series of LHR, whereas the proportion of malignant tumours has significantly increased in recent years (5)(6)(7). This is in agreement with the current practice not to increase the proportion of operations of benign liver tumours over standard levels seen in open procedures (8).…”
Section: Introductionmentioning
confidence: 99%
“…They include benign (adenoma and symptomatic focal nodular hyperplasia, haemangioma or giant liver cysts) and malignant (both primary and metastatic) lesions in the liver, and living donor liver harvesting. A high percentage of benign tumours was presented in early series of LHR, whereas the proportion of malignant tumours has significantly increased in recent years (5)(6)(7). This is in agreement with the current practice not to increase the proportion of operations of benign liver tumours over standard levels seen in open procedures (8).…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Laparoscopic liver resection was first reported in 1992, 3 but unlike other areas of abdominal surgery, this approach has been developed in a very limited number of institutions. [4][5][6][7][8][9][10] Except for a few studies, most of the articles reported a limited number of patients, but it has been established that in select patients, laparoscopic liver resections, if performed in institutions with expertise in hepatic surgery and advanced laparoscopic procedures, are safe, with results identical to those of open surgery. [5][6][7][8][9]11,12 Resection for benign liver disease can represent a valid indication for the laparoscopic approach because of the absence of risk of tumoral dissemination.…”
Section: Ost Indications Formentioning
confidence: 99%
“…7,10,12,20,21 The advantages of laparoscopic liver resections are those of all laparoscopic procedures. The reduction of the abdominal wall damage is associated with decreased postoperative pain, reduced peritoneal adhesions, shorter hospital stay, and an earlier return to previous activity.…”
Section: Commentmentioning
confidence: 99%
“…[82] In a prospective study Farges et al performed CT volumetry on patients undergoing pre-operative PVE and demonstrated that in those patients with no underlying parenchymal disease the typical increase in FLR was 16% whereas in those with chronic liver disease the typical increase in FLR was 9%. [83] In 2010 Wicherts et al reported a retrospective series of 67 patients who underwent liver resection for colorectal metastases after pre-operative PVE with a cohort of 297 patients who did not receive PVE. The authors observed that those patients treated with pre-operative PVE demonstrated a significantly higher complication rate (55.5% vs. 41.1%; p = 0.035) although there was no difference in surgical mortality between groups.…”
Section: Pre-operative Portal Vein Embolisationmentioning
confidence: 99%